Manoeuvrability investigation for tiltrotor aircraft with an integrated simulation engine - Yuan, Y.; Thomson, D.; Anderson, D. (My University, 2021)
The tiltrotor aircraft has unique flight dynamics characteristics because of the extensive aerodynamic interference effects present, the possibility of redundant control strategy, and the unique regime occurring during the conversion process, making its controllability more complex during manoeuvres. Also, these tiltrotor configurations are the basis for many Urban-Air-Mobility (UAM) prototypes, in which formation flight features and airworthiness regulation developments for UAM manoeuvring flight in urban areas should be considered. Therefore, this research developed an inverse simulation embedded manoeuvrability method for the tiltrotor aircraft, and this method was incorporated with the existing MAVERIC multi-agent system for the relevant UAM airworthiness investigation. First, the flight simulation model, the inverse simulation algorithm, and the MAVERIC system were introduced. Then, the Pop-up manoeuvre is utilised for the manoeuvrability investigation. The results indicate that the obtained control input is following the understood flight dynamics characteristics of the tiltrotor aircraft. Furthermore, the tiltrotor aircraft model and associated inverse simulation embedded analysis techniques were adapted into the MAVERIC system, which can be utilised to provide an intuitive demonstration of the manoeuvrability of tiltrotor aircraft. They will be an ideal platform for future UAV vehicles and relevant airworthiness investigations.